2019
DOI: 10.1002/bse.2373
|View full text |Cite
|
Sign up to set email alerts
|

Greenwashing and environmental communication: Effects on stakeholders' perceptions

Abstract: Since the first Earth Day in the 1970s, corporate environmental performance has increased dramatically, and cases of greenwashing have increased sharply. The term greenwash refers to a variety of different misleading communications that aim to form overly positive beliefs among stakeholders about a company's environmental practices. The growing number of corporate social responsibility claims, whether founded or not, creates difficulties for stakeholders in distinguishing between truly positive business perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
4
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 227 publications
(171 citation statements)
references
References 64 publications
6
138
4
5
Order By: Relevance
“…At the internal level, key concerns referred to investments in capital (Dodds et al, ), labor, and time (Pomarici et al, ), whereas the most important barriers linked to the external environment were the bureaucracy and the abuse of the sustainability concept (Szolnoki, ). The latter, also known as greenwashing, was even ranked second, after additional labor efforts, and is known to be a key challenge for wine industries (Berghoef & Dodds, ; Delmas & Grant, ; McEwan & Bek, ) as it may affect stakeholders' perceptions (Delmas & Burbano, ; Torelli, Balluchi, & Lazzini, ). The issue of greenwashing may also be related to another external barrier, namely, the lack of uniform norms, something which has also been stressed in literature (Mariani & Vastola, ; Pullman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the internal level, key concerns referred to investments in capital (Dodds et al, ), labor, and time (Pomarici et al, ), whereas the most important barriers linked to the external environment were the bureaucracy and the abuse of the sustainability concept (Szolnoki, ). The latter, also known as greenwashing, was even ranked second, after additional labor efforts, and is known to be a key challenge for wine industries (Berghoef & Dodds, ; Delmas & Grant, ; McEwan & Bek, ) as it may affect stakeholders' perceptions (Delmas & Burbano, ; Torelli, Balluchi, & Lazzini, ). The issue of greenwashing may also be related to another external barrier, namely, the lack of uniform norms, something which has also been stressed in literature (Mariani & Vastola, ; Pullman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One such method is to let parties rate them (Jøsang et al, 2007; Resnick & Zeckhauser, 2002), be it via third party evaluations, word of mouth (Dean & Lang, 2008), or expert endorsements (Klewes & Wreschniok, 2009). CS is another alternative for generating reputation (Miras‐Rodríguez, Carrasco‐Gallego, & Escobar‐Pérez, 2015; Delgado‐Márquez & Pedauga, 2017; Fanasch, 2019; Kim et al, 2009; Lai, Melloni, & Stacchezzini, 2016; Miras‐Rodríguez et al, 2017; Orlitzky, Schmidt, & Rynes, 2003; Park, 2018; Torelli, Balluchi, & Lazzini, 2019). In the case of the financial sector, CS strategies helped to restore damaged reputations in the aftermath of the 2008 financial crisis (Dell'Atti et al, 2017; Englert et al, 2018; Forcadell & Aracil, 2017a; Gallego‐Álvarez & Pucheta‐Martínez, 2019; Pérez & del Bosque, 2015).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Table S3), most of which might not count as high environmental impact industries. Research by Torelli et al (2019) found that stakeholders had higher perceptions of corporate greenwashing and stronger reactions to environmental scandals if the companies belonged to environmentally sensitive industries, such as mining, energy or chemicals. Therefore, companies in our sample might have felt to be under relatively low stakeholder scrutiny with subsequently lower greenwashing risk.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to benefits, firms could also experience disadvantages from an engagement for nature conservation. They might be accused of greenwashing (Torelli et al, 2019) or criticised for supporting conservation goals that are controversially discussed in society and politics (Krause & Matzdorf, 2019). H1 The more favourable the attitude towards nature conservation, the more likely a company's voluntary nature conservation engagement.…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation